Organocatalytic diastereoselective synthesis of spirooxindoles via [3+2] cycloadditions of azomethine ylides with α, β-unsaturated esters12. (2nd June 2017) - Peňaška, Tibor; Ormandyová, Kristína; Mečiarová, Mária; Filo, Juraj; Šebesta, Radovan
Abstract : Isatin-derived azomethine ylides react diastereoselectively with unsaturated esters to afford densely substituted spirooxindols. Abstract : An efficient three-component organocatalytic cascade 1, 3-dipolar cycloaddition reaction of in situ generated azomethine ylides with α, β-unsaturated esters is described. This reaction afforded a small library comprised of 20 new highly substituted spirooxindole derivatives. The products were obtained in yields up to 76%, usually as single diastereomers. A range of different hydrogen bond donor, Brønsted basic or acidic organocatalysts were tested. Bifunctional thioureas and squaramides were identified as competent catalysts for this transformation. The effect of microwave irradiation, as well as solvent-free conditions, was also examined.